Sámi knowledge and ecosystem-based adaptation strategies for managing pastures under threat from multiple land uses - Hausner, Vera Helene; Engen, Sigrid; Brattland, Camilla; Fauchald, Per (Journal of Applied Ecology, 2020)
Ecosystem‐based adaptation (EbA) relies upon the capacity of ecosystems to buffer communities against the adverse impacts of climate change. Maintaining ecosystems that deliver critical services to communities can also provide co‐benefits beyond adaptation, such as climate mitigation and protection of biological diversity and livelihoods. EbA has, to a limited extent, drawn upon indigenous and local knowledge for defining critical services and for implementing EbA in decision‐making. This is a paradox given that the primary focus of EbA is to enable communities to adapt to climate change. The purpose of this study was to elucidate EbA strategies that take into account the knowledge of Sámi reindeer herders about pastures in tundra regions. We first examined what constitutes critical services through a synthesis of data and literature. We thereafter used content analysis of 91 land use cases from 2010 to 2018 to investigate to what extent the herders’ knowledge and maps over seasonal pastures and migratory routes are used in local decision‐making. Finally, we propose EbA strategies of relevance to Sámi communities and pastoral communities elsewhere. Our analysis revealed that reindeer herders and organizations representing their interests perceived threats from green energy development, tourism, recreation, public road construction and powerlines. These threats included the loss of key habitats and the loss of connectivity for migration between seasonal pastures. Pastoralists’ knowledge is incorporated through participatory tools to protect the ecosystems and services crucial for pastoralists, but multiple competing land uses result in incremental loss of pastures regardless. Synthesis and applications . Protecting pasture ecosystems and the services they deliver, including the connectivity between pastures, are necessary Ecosystem‐based adaptation (EbA) strategies to buffer the adverse effects of climate change. Drawing on pastoralists’ knowledge to elicit EbA strategies can inform decision‐making, but it is equally important to implement this knowledge for prioritizing adaptation needs in the assessment of competing land use.